SUNTIK 3 BULAN DI PUSKESMAS BAAMANG II SAMPIT KABUPATEN KOTAWARINGIN TIMUR PROVINSI KALIMANTAN TENGAH TAHUN 2021 - dewi sartika (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2022)
ABSTRACT Background : The Family Planning Movement is one of the efforts to improve the welfare of mothers and children as well as to create a happy and prosperous small family. Injectable family planning is the most widely used contraceptive by women of childbearing age. The high acceptor of 3-month injection KB is influenced by several factors, namely age, education, occupation, number of children. Based on the results of a preliminary study conducted by researchers at the Baamang II Sampit Health Center on September 14, 2021, the number of mothers who had 3 months of family planning injections in 2021 was 86 people.. Objectives : To describe the Factors of the High Akseptor KB Suntik 3 Months in Puskesmas Baamang II Sampit Kotawaringin Timur, Central Kalimantan Province in the Year 2021. Methods : This research was conducted with a descriptive survey research type. Survey research is a study conducted at the Baamang II Sampit Public Health Center in January-May 2021 with a sample of 86 people using random sampling technique from secondary data Univariate analysis The Results : Based on the outcome factors of mothers who underwent 3-month family planning injections at the Baamang II health center in 2021, the majority of mothers were 47 people (54,7%) at risk, 39 people (45,3%). Based on education, primary education was 21 people (24.4%), junior high school was 18 people (20.9%), high school was 46 people (53.5%), university was 1 person (1.2%). Based on the work of IRT as many as 54 people (62.8%), private as many as 19 people (22.1%), self-employed as many as 13 people (15.1%), civil servants as many as 0 (0%). Based on the number of children of mothers who are less than 2 as many as 42 people (48.8%), more than 2 as many as 44 people (51.2) Conclusion : There are 86 mothers who did the 3-month family planning injection at the Baamang II Health Center in Sampit in 2021 Keywords : Age , Education , Occupation , Number Of Children (1) Lecturer Of Midwifery Academy Muhammadiyah Kotim (2) Student Of Midwifery Academy Muhammadiyah Kotim